CLINICAL AND IMMUNOLOGICAL FEATURES OF VARIOUS FORMS OF GLOMERULONEPHRITIS (Modern American Journal of Medical and Health Sciences, 2025)
Background. Glomerulonephritis is characterized by marked clinical heterogeneity, largely determined by dysregulation of cytokine-mediated immune responses